Injection-moulding of nitrogen-foamed bio-based microcellular poly(butylene succinate): Processing conditions/foam structure/flexural properties relationship. Issue 1 (February 2020) - Ykhlef, Nazim; Lafranche, Eric
This paper aims to identify the main processing parameters that optimize as well the microcellular structure (cell size, cell density) of nitrogen (N2 ) foamed injection-moulded poly(butylene succinate) (PBS) as the resultant flexural properties of the part. The part beam geometry was designed so as to reproduce some geometrical shapes (e.g. thickness change, ribs, bosses or holes) occurring on most of industrial parts. A Taguchi L9 design of experiments (DOE) has been first used to quantify the effects of processing conditions on microcellular structure and mechanical performances. Among the processing parameters, the melt temperature, gas content, injection volumetric flow rate and back pressure were chosen for the DOE due to their level of influence on gas dissolution and nucleation phases. An analysis of variance (ANOVA) showed that the microcellular structure depended mainly on nitrogen content and, to a lesser extent, on back pressure representation of gas pressure saturation in the PBS/N2 system during the feeding stage. The resultant specific flexural properties were controlled by the skin/core ratio as well as the finesse of foam structure (cell sizes, cell density) but a 15% loss in specific performances was noted compared with the unfoamed part. The microcellular structure/mechanical performances could be thus established from the microstructure analysis. In a second step, the foamed microcellular structure has been improved by introduction of micro-talc in the PBS acting as cell nucleating agent (heterogeneous nucleation). A significant increase in cell density and cell reduction (40%) were observed.